Stripe rust resistance in historical wheat cultivars at seedling and adult plant stages and tagging effective resistance genes using molecular markers - Majeed, Khawar; Sufyan, Muhammad; Abbasi, Kainat; Ahsan, Rafia; Bux, Hadi; Zakria, Muhammad; Fayyaz, Muhammad; Mirza, Javed Iqbal; Ali, Mohsin; Rasheed, Awais; Zhonghu, He (Springer Nature, 2025)
We examined 189 historical wheat cultivars from Pakistan released during 1910 to 2021 for stripe rust resistance at the seedling and adult plant stages. The cultivars were further characterized for the presence of known stripe rust resistance genes and QTL using 6 gel-based and 20 KASP markers. Seedling screening against five Pst races revealed that 10 cultivars were resistant to all five races. Field screening at six locations over two crop seasons identified 30 (15.7%) cultivars as resistant, 31 (16.4%) cultivars as susceptible across locations, and the remaining showing varying response at different locations. The durable rust resistance genes Yr18, Yr29, Yr30, and Yr46 were present in 23.6%, 74.3%, 4.7% and 5.2% cultivars, respectively. Some effective all stage resistance (ASR) genes like Yr57 and Yr48 was present only in four and two cultivars, respectively. The allelic effects of durable rust resistance gene Yr46, and other adult plant resistance (APR) genes Yr78 and Yr80 significantly reduced the stripe rust severity across locations. Many ASR genes like Yr9, Yr24/Yr26, and Yr44, were present, but they were virulent to any or multiple Pst isolates. The genes present in nine ASR and ten APR wheat cultivars need to be identified for breeding rust resistant cultivars. This is the first comprehensive study about the stripe rust resistance at seedling and adult plant stages and tagging known Yr resistance genes in wheat cultivars of Pakistan representation more than 110 years of wheat cultivation history.